"Follow the Tree Flowers": Fugitive Mapping in Beloved. Issue 1 (8th October 2020) - Kelley, Elleza
Abstract: This article attempts to analyse mapping practices at the intersection of geography, black studies and literary studies, in order to reassess the political and pedagogical possibilities of mapping under late capitalism. I turn to Toni Morrison's novel Beloved to track black cartographic practices otherwise obscured or, as Katherine McKittrick writes, "rendered ungeographic". The novel offers a hidden and unauthorised archive for the often clandestine geographic practices that make possible fugitivity from the mechanics of "slaveholding agro‐capitalism" and its ongoing legacy. As an unofficial archive of black geographic practice, Morrison's novel might itself be thought of as a map: a contemporary mode of memorialising the depth of place, relation, and navigation—a depth no two‐dimensional map can accommodate. Finally, this article demonstrates the valuable interventions that black studies and black creative production can make within the subfields of critical cartography and critical geography.